Assessment of the electrodeposition synthesized manganese chromite and cobalt‑nickel layered double hydroxide composite for high-performance supercapacitor applications. (February 2023) - Rutavi, Gift; Tarimo, Delvina Japhet; Maphiri, Vusani Muswa; Kitenge, Vianney Ngoyi; Manyala, Ncholu
Abstract: Cyclic voltammetry (CV) electrodeposition synthesis was performed twice to synthesize manganese chromite (MnCr2 O4 -ϕ) on NF, where −1.4 ≤ ϕ ≤ − 1.0 is the lower voltage (V vs Ag/AgCl) set in the CV during electrodeposition, the higher potential being 0.5 V. This was followed by another electrodeposition of cobalt nickel layered double hydroxide (CoNi-LDH) on MnCr2 O4 -ϕ. The unique layered structure of CoNi-LDH produce electrodes with excellent electrochemical performance. MnCr2 O4 –1.2 V@CoNi-LDH (ϕ = − 1.2 (V vs Ag/AgCl)) yielded the best electrochemical performance in three-electrode set-up in 2 M KOH with the highest specific capacity of 1529.3 C g −1 at a specific current of 1 A g −1 . This electrode was incorporated into the hybrid device with activated carbon (AC) from Amarula Husk as the negative electrode (AMH). The device (MnCr2 O4 -1.2 V@CoNi-LDH//AMH) produced a superb specific energy of 80.2 Wh kg −1 corresponding to a specific power of 1117.7 W kg −1 at 1 A g −1 . The device also showed the capacity retention and Coulombic efficiency of the device were 72.9 and 99.7 %, respectively after 15, 000 GCD cycles at 9 A g −1 . Due to the phenomenal performance, the produced materials are suitable candidates for high energy supercapacitor applications. Highlights: MnCr2 O4 -1.2 V@CoNi-LDH//AMH was synthesized by successive electrodepositions. MnCr2 O4 -1.2 V increased the conductivity and the structural stability of CoNi − LDH. MnCr2 O4 -1.2 V@CoNi-LDH was used as a positive electrode of the asymmetric device. MnCr2 O4 -1.2 V@CoNi-LDH//AMH device was fabricated with AMH as negative electrode. High specific energy and power of 80.2 Wh kg −1 and 1117.7 W kg −1 were recorded.